A procedure for the parametric identification of viscoelastic dampers accounting for preload - Lépore Neto,Francisco Paulo (2012)
Passive vibration isolators are usually made of viscoelastic materials. These materials have non-linear characteristics that change their dynamical properties with temperature, frequency and strain level. The vibration isolator's mathematical modeling and optimal design require the prior knowledge of the stiffness and damping of the applied viscoelastic material. This work presents a dynamical characterization methodology to identify the stiffness and damping of three samples of viscoelastic rubber with hardness of 25, 33 and 48 SHORE A. The experimental apparatus is a one-degree of freedom vibratory mechanical system coupled to the viscoelastic damper. Sweep sine excitations are applied to the system and the resulting forces and vibration levels are measured. The amplitude of the excitation is controlled to achieve a constant RMS level of strain in the viscoelastic samples. The experimental results are obtained for conditions of no pre-strain and with a 10% of prestrain. The time domain data is post-processed to generate frequency response functions that are used to identify the damping and stiffness properties of the viscoelastic damper.